Modeling Behavioral Intentions: Exploring Factors Using IPMA via Trust and Customer Satisfaction in Gojek Indonesia - Alamsyah, Rachel Anggraini; Hendayani, Ratih; Hidayah, Riski Taufik (Asosiasi Dosen Peneliti Ilmu Ekonomi dan Bisnis Indonesia, 2024)
Online transportation service has become a common method of commuting for the majority of people. It offers convenience and comfort to meet people's needs. The purpose of this study is to assess the perception of service quality driver’s online transportation Gojek Indonesia, by examining the impact of service quality and customer perceived value on users' behavioral intentions, both directly and mediated by trust and customer satisfaction. Data were collected from 400 respondents who used Gojek services in Indonesia through a structured questionnaire. The method utilized is Structural Equation Modeling (SEM) using SmartPLS 3.2.9 software. Research findings suggest that customer perceived value, service quality, trust, and customer satisfaction play significant roles in behavioral intention. Service quality and customer perceived value positively impact behavioral intentions, both directly and through the mediation of trust and customer satisfaction. Enhanced levels of customer perceived value and service quality will elevate users' intentions to utilize Gojek services again. These findings contribute to expanding the SERVQUAL model by integrating behavioral intention with trust and customer satisfaction. The novelty lies in the influence of customer perceived value on behavioral intentions mediated by trust and customer satisfaction. The study provides insights for companies to understand the importance of service quality factors and perceived customer value for long-term benefits of achieving competitive advantage.